"I did it my way". Issue 1 (2nd January 2016) - Roe, David
ABSTRACT: In this Festschrift for John S. Strauss, a number of his profound contributions and their impact over time are highlighted, while reflecting upon his journey of discovery through my own personal journey, beginning as a PhD student of his in the 1990s.